2023
DOI: 10.1186/s13244-023-01450-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging accuracy in size determination of prostate cancer in men undergoing radical prostatectomy for clinically localised disease

Wael Ageeli,
Nabi Soha,
Xinyu Zhang
et al.

Abstract: Objectives To compare the accuracy of pre-surgical prostate size measurements using mpMRI and USWE with imaging-based 3D-printed patient-specific whole-mount moulds facilitated histopathology, and to assess whether size assessment varies between clinically significant and non-significant cancerous lesions including their locations in different zones of the prostate. Methods The study population included 202 men with clinically localised prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…1A ). It has been reported that S-DWI cannot accurately determine tumor size ( 13 ), and serial biopsies are performed during AS to assess tumor grade and estimate tumor burden. These biopsies are uncomfortable, and come with significant risks, such as a 4% hospitalization rate due to complications that include sepsis and rectal bleeding when performed transrectally ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…1A ). It has been reported that S-DWI cannot accurately determine tumor size ( 13 ), and serial biopsies are performed during AS to assess tumor grade and estimate tumor burden. These biopsies are uncomfortable, and come with significant risks, such as a 4% hospitalization rate due to complications that include sepsis and rectal bleeding when performed transrectally ( 14 ).…”
Section: Introductionmentioning
confidence: 99%